Epicardial adipose tissue in a coronary artery disease patient - Sibashankar Kar (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Thick Epicardial Adipose Tissue (EAT) is not always a finding at operation theatre in patients undergoing Coronary Artery Bypass Grafting (CABG). But epicardial fat has a direct relationship with obesity and metabolic syndrome. Its presence is an independent risk factor for Coronary Artery Disease (CAD). Intraoperative fi nding is an indicator for post-operative weight reduction and early initiatio pharmaceuticals to prevent progression of native vessel disease.